2(x+3y)-4(2x-8y)=

Simple and best practice solution for 2(x+3y)-4(2x-8y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3y)-4(2x-8y)= equation:


Simplifying
2(x + 3y) + -4(2x + -8y) = 0
(x * 2 + 3y * 2) + -4(2x + -8y) = 0
(2x + 6y) + -4(2x + -8y) = 0
2x + 6y + (2x * -4 + -8y * -4) = 0
2x + 6y + (-8x + 32y) = 0

Reorder the terms:
2x + -8x + 6y + 32y = 0

Combine like terms: 2x + -8x = -6x
-6x + 6y + 32y = 0

Combine like terms: 6y + 32y = 38y
-6x + 38y = 0

Solving
-6x + 38y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-38y' to each side of the equation.
-6x + 38y + -38y = 0 + -38y

Combine like terms: 38y + -38y = 0
-6x + 0 = 0 + -38y
-6x = 0 + -38y
Remove the zero:
-6x = -38y

Divide each side by '-6'.
x = 6.333333333y

Simplifying
x = 6.333333333y

See similar equations:

| 2(x-3)+5=3(z-1) | | Z(2z-9)(z+3)=0 | | 0.6(x+20)+08(x-10)=46 | | 5x-2(x+3)=40 | | 10=40-3x | | 6x-4x+13=27+2x | | (2x+3)(x+1)-3(x+2)(x+1)=-3(x+5) | | 100g+8= | | 6(94X-8)+3X=141 | | 9+g=-14 | | (9+j)= | | -10n+20+2n+6= | | 347=3s-13 | | -16=2(1+14) | | 3x^2+12x-1440=0 | | 17x-45x=28 | | 28-3u=u | | 2(x+y)-2y= | | -16=2(x+14) | | 4n-24=-20 | | -20x=-4x-8 | | -10-9x+6x-60= | | b(-2)=18-0.5(-2) | | 0=-1.6t^2+160 | | n^3-4n^2=-4 | | 8=-45+b | | x^2+5xy+y^4=7 | | -54m-27+6+24m= | | 3(2x-15)=6x-45 | | 6n+5=66 | | 3=543 | | 9a+60a-10+40a= |

Equations solver categories